(untitled) (CAHIERS MAGELLANES-NS, 2024)
The purpose of this study is to ascertain how consumers of Mayiladuthurai District in Tamil Nadu feel about mobile service providers. To accomplish the objectives, a descriptive study was carried out. A well-structured questionnaire with a list of statements about various products, services, and facilities was completed by 150 respondents in total. The statements included information about voice clarity, customer care, brand image, network connectivity, call tariff, service quality, sales promotion offers, value-added services, and billing information from the service provider. In this work, the chi-square test is used to verify the accuracy of the information provided by the participants. The purpose of this study is to make recommendations to the telecom industry on network quality, call dropouts, coverage, call rate, and connectivity.